Prospects for applying the dendrochronological method to ethno-ecological studies of Tuvan historical and cultural heritage - Mainicheva, Anna Yurievna; Myglan, Vladimir Stanislavovich; Filatova, Maya Olegovna (The New Research of Tuva, 2020)
The dendrochronology method is an integral part of researching the reconstruction of environmental conditions in the past, and the calendar-based (relative) dating of historical and cultural monuments. In the Republic of Tuva dendrochronological studies have been ongoing since 1974. This explains the need for data classification in existing tree-ring timelines and collections of archaeological wood. The article examines the results and prospects of dendrochronological studies of historical and cultural Tuvan heritage. Sources for the study are drawn from the databank of dendrochronological studies of Tuvan heritage, set up by the authors. The analysis has shown that dendrochronological research is largely associated with the study of the high-mountainous regions of the republic (Mongun taiga, the Sangilen highlands) where it was possible to build some thousand-year tree-ring timelines. The steppe part of the republic is rather understudied, although it is there that world-famous archaeological sites and architectural heritage are located. The sample collections of archaeological wood from the barrows are rather fragmented and have not so far been studied using the dendrochronological method. Usually they were carbon-dated, however, this does not always make it possible to accurately determine their calendar age. The reason is that the dates fall on a “plateau” on the carbon calibration curve, or dating ignores the tree’s own age relative to the site. The classification of dendrochronological data revealed two aspects of utter importance: 1) it is currently possible to create a tree-ring timeline of the first millennium BC; 2) the existing network of tree-ring timelines makes it possible to conduct large-scale research on the architectural heritage of the Republic of Tuva.